2019
DOI: 10.1108/lht-02-2018-0025
|View full text |Cite
|
Sign up to set email alerts
|

Investigating user continuance intention toward library self-service technology

Abstract: Purpose The purpose of this paper is to apply expectation-confirmation theory (ECT) and the unified theory of acceptance and use of technology (UTAUT) to identify potential determinants of library patrons’ intention to continue using (continuance) self-issue and return systems for borrowing and returning books. The role of continuance is specifically interesting and is well-established in the literature of information systems (ISs) and marketing because continuance is considered to be the central element for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 50 publications
(68 reference statements)
0
8
0
1
Order By: Relevance
“…UTAUT is a development of technology acceptance model, also its effectiveness in illustrating digital platform system acceptance are shown by other previous investigations. The forecasting capability of UTAUT has been confirmed through various information technology platforms adoption, such as online banking (Martins, 2014;Le et al, 2019); library self-service (Wu, 2018); tablet device (Magsamen, 2015); and mobile wallet (Chawla, 2019). However, based on past research, the author could add some new factors to enhance its explanatory power based on specific context.…”
Section: Literature Reviewmentioning
confidence: 99%
“…UTAUT is a development of technology acceptance model, also its effectiveness in illustrating digital platform system acceptance are shown by other previous investigations. The forecasting capability of UTAUT has been confirmed through various information technology platforms adoption, such as online banking (Martins, 2014;Le et al, 2019); library self-service (Wu, 2018); tablet device (Magsamen, 2015); and mobile wallet (Chawla, 2019). However, based on past research, the author could add some new factors to enhance its explanatory power based on specific context.…”
Section: Literature Reviewmentioning
confidence: 99%
“…These model include the Technology Acceptance Model (TAM) developed by (Davis, 1989), Unified Theory of Acceptance and Use of Technology (UTAUT) developed by (Venkatesh et al, 2003), and information system success model (DeLone & McLean, 1992). Many researchers have used TAM to understand the intentions and behaviors of the use of information technology by users in the context of learning (Camilleri & Camilleri, 2019;Kardoyo et al, 2015;Lestari & Indrasari, 2019;Schöpfel et al, 2019), UTAUT (Muhsin et al, 2016;Samsudeen, 2019;Wu & Wu, 2019) and ISSM (Chen et al, 2016;Huang et al, 2015;Masrek & Gaskin, 2016).…”
mentioning
confidence: 99%
“…UTAUT model indicated that EE positively influence behavioral intention of use the technology (Venkatesh et al, 2003). While other studies supported the positive link between EE and behavioral intention (Alhassany & Faisal, 2018), Zhou et al (2010 as well Yu (2012) perceived adversely (Wu & Wu, 2019). In fact, the relationship between EE and behavioral intention has been debated regularly following their effect toward SST.…”
Section: The Influence Of Effort Expectancy (Ee) On Behavioral Intention Toward Sstmentioning
confidence: 98%